The effect of drying time and maceration temperature on the anthocyanin content of telang flower extract (Clitoria ternatea L.): Pengaruh lama pengeringan dan suhu maserasi terhadap kadar antosianin ekstrak bunga telang (Clitoria ternatea L.) - Eko Febrianto; Nanik Suhartatik; Merkuria Karyantina (Agrobiotek, 2025)
Indonesia is rich in biodiversity, there are around 40,000 species of plants, and they have different uses,such as traditional medicine, can be made into handicrafts, used as decorations, used as natural dyes. Butterflypea flowers have the potential as a natural dye because the anthocyanins contained in their petals emit a bluecolor. The purpose of this study was to determine the anthocyanin content in butterfly pea flowers using themaceration extraction method which is commonly used to determine the best anthocyanin concentration. Thisstudy used a completely randomized factorial design (CRD), namely drying time, (fresh, 1, 2 days) andmaceration temperature (50, 60, 70oC), so that 9 combinations were obtained and each treatment was repeatedtwice. The results of this study indicate that the longer the drying time and the higher the macerationtemperature, the higher the levels of anthocyanin, total phenol, and the darker the color. The researchconducted showed that the best treatment combination was the drying time of 2 days with a macerationtemperature of 70Â°C to produce butterfly pea flower extract which had antioxidant activity of 54.66%, totalphenol 4.16 KTF (mgGAE/g), anthocyanin 123.48 mg/g, pH 6.03. Color sensory test analysis was 4.5 andwater content of butterfly pea flower was 10.79%. The optimal drying time and maceration temperature willproduce high total phenol and anthocyanin levels. Butterfly pea flowers have high levels of anthocyanins, sothey have the potential to be studied further.